Bioresorbable scaffolds vs. drug-eluting stents for patients with myocardial infarction: A systematic review and meta-analysis of randomized clinical trials - Liu, Yong; Xiao, Di; Wu, Yang; Li, Meng; Liu, Jia; Zhuang, Rui; Ma, Liyong; Li, Jingen; Zhang, Lijing (Frontiers in Cardiovascular Medicine, 2022)
Objective: To compare the long-term efficacy and safety of bioresorbable scaffolds (BRS) with drug-eluting stents (DES) in patients with myocardial infarction (MI) undergoing percutaneous coronary interventions (PCI). Methods: We did a systematic review and meta-analysis of randomized controlled trials (RCTs) in which patients were randomly assigned to BRS or DES and followed up for at least 12 months. We searched PubMed, CENTRAL, EMBASE, and Web of Science from inception to March 1, 2022 to identify relevant studies. The primary outcome for this study was the device-oriented composite endpoint (DOCE) consisting of cardiac death, target-vessel myocardial infarction (TVMI), and target lesion revascularization (TLR). Secondary outcomes were a composite of major adverse cardiac events (MACE, all-cause death, TVMI, or target vessel revascularization [TVR]) and the patient-oriented composite endpoint (POCE, defined as a composite of all-cause death, MI, or revascularization). The major safety measures were definite/probable device thrombosis and adverse events (AEs). Results: Four randomized clinical trials with 803 patients were included in this analysis.The mean age of the participants was 60.5±10.8 years and the majority of them were men (81.9 %). Patients treated with BRS had a higher risk of DOCE (RR 1.62, 95% CI: 1.02–2.57, P = 0.04) and MACE (RR 1.77, 95% CI: 1.02–3.08, P =0.04) compared with patients treated with DES. No significant difference on the event definite/probable device thrombosis (RR 1.31, 95% CI: 0.46–3.77, P = 0.61) and POCE (RR 1.33, 95% CI: 0.89–1.98, P = 0.16) were observed between BRS and DES. No treatment-related serious adverse events were reported. Conclusion: In patients undergoing PCI for MI, BRS was associated with a higher risk of DOCE and MACE compared with DES. In addition, BRS implantation showed a non-signiﬁcant increase on the definite/probable device thrombosis.